Crosspteryx fibrifuga leaf extract enhances host resistance to Trypanosoma congolense infection in mice by regulating host immune response and disrupting the activity of parasite superoxide dismutase enzyme - Ikeogu, Nnamdi; Olayinka-Adefemi, Folayemi; Edechi, Chidalu; Onyilagha, Chukwunonso; Jia, Ping; Marshall, Aaron; Ode, Julius; Uzonna, Jude (Frontiers in Microbiology, 2023)
African trypanosomiasis, a neglected tropical disease, is caused by diverse species of the protozoan parasite belonging to the genus Trypanosoma. Although anti-trypanosomal medications exist, the increase in drug resistance and persistent antigenic variation has necessitated the development of newer and more efficacious therapeutic agents which are selectively toxic to the parasite. In this study, we assessed the trypanocidal efficacy of Crosspteryx fibrifuga leaf extract (C.f/L-extract) in vitro. Following treatment of T. congolense parasites with C.f/L-extract, we observed a significant decrease in parasite number and an elevation in the expression of the apoptotic markers, Annexin V and 7-Aminoactinomycin D (7AAD). Interestingly, at the same concentration (50 µg/ml), C.f/L-extract was not cytotoxic to murine whole splenocytes. We also observed a significant increase in pro-inflammatory cytokines and nitric oxide secretion by bone marrow derived macrophages following treatment with C.f/L-extract (10 µg/ml and 50 µg/ml) compared to PBS treated controls, suggesting that the extract possesses an immune regulatory effect. Treatment of T. congolense infected mice with C.f/L-extract led to significant decrease in parasite numbers and a modest increase in mouse survival compared to PBS treated controls. In addition, there was a significant increase in CD4 + IFN- + T cells and a decrease in CD4 + IL-10 + T cells in the spleens of T. congolense infected mice treated with C.f/L-extract. Interestingly, C.f/L-extract treatment decreased the activity of superoxide dismutase (an enzyme that protects unicellular organisms from oxidative stress) in T. congolense parasites but not in splenocytes. Collectively, our study has identified C.f/L-extract as a potential anti-trypanosomal agent that warrant further investigation and possibly explored as a treatment option for T. congolense infection.